Screening and identification of protein interacting with goose astrovirus - Qian, Lingling; Liu, Yuwei; Wang, Xiaochun; Yang, Shixing; Ji, Likai; Sun, Xiaopeng; Wang, Jianqiang; Shan, Tongling; Zhang, Wen; Shen, Quan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionGoose Astrovirus (GoAstV), a recently identified member of the Astroviridae family in China, predominantly affects goslings, resulting in substantial economic losses to the goose farming industry due to its high infection and mortality rates. Currently, the infection mechanism and pathogenesis of GoAstV remain unknown.MethodsGiven this, the Viral Overlay Protein Blot Assay was utilized to identify and characterize proteins on the LMH (Leghorn Male Hepatoma) cell membrane that interact with Goose Astrovirus. The identities of the candidate proteins were determined via LC-MS mass spectrometry analysis, bioinformatics analysis, and UniProt database search. The interaction between HSPA5 and the astrovirus protein was further validated in vitro through Western blot and Coimmunoprecipitation experiments. Finally, bioinformatics tools such as SWISSMODEL, AlphaFold, and ZDOCK were employed to construct and analyze the docking complex model between the candidate protein and GoAstV protein, including their key binding residue sites.ResultsWe successfully identified a 70 kDa protein in the plasma membrane protein extracts of LMH cells and confirmed the identity of this candidate protein as HSPA5. Meanwhile, in vitro experiments further validated the interaction between HSPA5 and astrovirus proteins. Subsequently, we successfully predicted the docking complex model of HSPA5 protein with GoAstV protein. Further prediction of the binding residue sites revealed that seven residues of the GoAstV-P2 protein (THR124, ILE22, VAL24, TRP51, PRO66, GLN100, and VAL125) and twelve residues of the HSPA5 protein (ARG2, HIS3, LEU4, LEU6, ALA7, LEU8, LEU9, LEU10, LEU11, ASP411, VAL413, and LEU415) may be involved in the interaction between these two proteins.DiscussionOur research results have preliminarily elucidated the interaction mechanisms between viral proteins and receptors, facilitating exploration from multiple angles of the roles of candidate protein in the process of GoAstV infecting host cells. This provides a theoretical basis for further identification of GoAstV receptors and clarification of its infection mechanisms.